Thursday

April 24, 2014

April 24, 2014

Posted by **alex** on Monday, September 17, 2012 at 1:24am.

- Algebra -
**Bosnian**, Monday, September 17, 2012 at 1:35am( 9 a ^ 3 b ^ 4 - 12 a ^ 2 b ^ 5 + 6 a b ^ 7) / ( 6 a ^ 2 b ^3 ) =

3 * a * b ^ 3 * ( 3 a ^ 2 * b - 4 a * b ^ 2 + 2 b ^ 4 ) / [ 3 * a * b ^ 3 * ( 2 a ) ] =

( 3 a ^ 2 b - 4 a b ^ 2 + 2 b ^ 4 ) / 20

- Algebra -
**Bosnian**, Monday, September 17, 2012 at 1:37amSorry last row :

= ( 3 a ^ 2 b - 4 a b ^ 2 + 2 b ^ 4 ) / 2 a

**Related Questions**

Algebra - (3a^2+6ab-a-2b)/(9a^2-6a+1)

algebra - how do i figure: (-12a^2b^6)^3 over (9a^3b^9)^3

Algebra, please help quick - simlify the following to the lowest terms: (a) [x^2...

Math - Factor completely. 36a^3b^2+66a^2b^3-210ab^4 Is this correct? 6ab^2(6a^2+...

math - 3a^2b + 6a^2b 9a^4b^2

dividing with polynomials - solve by using polynomial division(16ab^3c-10ab^2c^2...

MATH Matrix Equation - If 4a + 3b + c = 27 3a + b + 4c = 16 9a + 2b + 3c = 33 ...

Math Matrix EQ - If 4a + 3b + c = 27 3a + b + 4c = 16 9a + 2b + 3c = 33 then 2a...

Pre-Calc-please check - Please check this for me expand (3z-2b)^5 using Binomial...

Pre-Calc - Please help me solve these two equations!! Divide and express as a ...